Optimasi Penataan Barang pada Proses Distribusi Menggunakan Algoritme Evolution Strategies - Rani Kurnia; Wayan Firdaus Mahmudy (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Distribution is the one of important processes in industrial activities such as goods's distribution. But unfortunately, this process is one of processes that spend much expense. Then it be required a great management to minimize costs for that's process. One of them is to optimization the goods organize management. Optimization problem of goods organize management can be solved using evolution strategies algorithm that known as a simple algorithm that can be solved a complex problems. In this case, evolution strategies algorithm start with raising the random individu, then mutation process, then do the goods organize management process to get the fitness result and close with selection process to get the great individu. Based on the test of goods organize management that have been process with 50 goods, it get the optimal parameter consist of population 60, lambda 18, offspring 18Î¼, and generation 15 with the fitness's average is 2,404. The final result of this experiment is a scheme of the optimal solution for goods organize management in vehicle.